KAMUS BALI-INDONESIA BIDANG ISTILAH JUDI DENGAN SARANA UANG KEPENG DAN DADU DI BALI - I Wayan, Budi Utama (Humanis; Volume 12. No.2. Agustus 2015, 2015)
Research "Bali - Indonesia dictionary term field Gambling With Money Means Kepeng and Dice in Bali" aims to determine the shape and number of terms contained in gambling by means kepeng and dice in Bali. The theory used is the theory of Structural Linguistics, developed by Ferdinand de Saussure, the theory Lexicology and lexicography. The method used in the step of providing data, namely: structured interview method and see, with a technique that is: the tapping technique followed by recording technique and technique note. In the data analysis stage, use the method that is equivalent to the part: translational methods followed the basic techniques, namely: sorting the decisive element with subsequent engineering, circuit engineering equate appeal and appeal circuit techniques equalize the subject matter. Used also agih method with the basic techniques , namely: for the element directly down to the two types of advanced techniques, namely: engineering and engineering expanded inline. The method used in the presentation of the results of the analysis are formal and informal methods with techniques inductive and deductive thinking. The results of this study are the terms which form the basis of words comprising: a base word monosyllabic, disyllabic word base, and the base of the three tribes. Said derivative comprising: said affixed ie, prefixes N, {m?-}, {p?N-}, {m?N-}, suffix {-an}, and affixes join, repeated words consisting of: reduplication intact, intact reduplication + affixes, partial reduplication + affixes, and compound words based on the type of said comprising: Noun + Noun, Noun + verb, Noun + Adjectiva, Adjectiva + Noun, verb + Numeral . The term is shaped phrases: endosentris phrase one central comprising: a noun phrase, the phrase adjektival, and the verbal phrase. The term is shaped clause: clause endosentrik. This study was able to collect as many as 208 terms.
Keywords: dictionary , terms , gambling